2007
DOI: 10.1586/17469872.2.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicines: use in skin diseases

Abstract: There is a plethora of complementary and alternative medicines (CAM) used by sufferers of skin diseases. For the most part, the use of these therapies is based on anecdotal evidence or on traditional patterns of use. Relatively little empirical evidence exists for the use of CAM therapies in skin diseases. Those studies that have examined CAM skin disease therapies have often been flawed methodologically. A small number of CAM therapies have been accepted or are on the cusp of acceptance in dermatological prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 115 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…It is evident that CAMs are used by a large part of the population. When they are used together with conventional medicine (Magin & Adams 2007;Noiesen et al 2007), it may be difficult to ascertain therapeutic benefits from either type of medicine and identify adverse effects and drug interactions. The combination of CAM with conventional medicines can affect the overall clinical outcome as this often leads to non-compliance with prescribed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that CAMs are used by a large part of the population. When they are used together with conventional medicine (Magin & Adams 2007;Noiesen et al 2007), it may be difficult to ascertain therapeutic benefits from either type of medicine and identify adverse effects and drug interactions. The combination of CAM with conventional medicines can affect the overall clinical outcome as this often leads to non-compliance with prescribed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review (SR) of epidemiological studies, revealed an increasing prevalence in Africa with approximate doubling of lifetime prevalence in South Africa (SA) (Deckers et al, 2012). Numerous studies have demonstrated the increased use of complementary and alternative medicine (CAM) amongst dermatological patients (Baron et al, 2005;Buchar et al, 2012;Eisenberg et al, 1998;Magin & Adams, 2007). Atopic eczema was reported to be the most frequent dermatological condition where CAM was sought (Baron et al, 2005;Bielory & Lupoli, 1999;Ernst, 2000).…”
Section: Introductionmentioning
confidence: 99%